The Extent of E-Business Usage and Perceived Cumulative Benefits: A Survey on Small and Me-dium-Sized Enterprises - Mohamad, Rosli (Information Management and Business Review, 2013)
Internet-based application (e-business) is well-recognized as a useful mean to extend business efficiency. Owing to the idiosyncratic nature of Small and Medium-sized Enterprises (SMEs), considerable works have been initiated to explain why firms within this sector embrace e-business. Despite extensive research to identify factors that explain the firm’s e-business practice, works are still limited to examining as to what extent the e-business assimilates into business operation. Furthermore, firms would experience varying degrees of benefits by deploying e-business. Therefore, this paper reports intensity of ebusiness usage across various business processes and its relationship with cumulative benefits. A survey of 140 SMEs has revealed the diversity of e-business usage across business processes. A cluster analysis has further proposed three distinct profiles of firms based on the intensity of their e-business usage. Finally, the empirical evidence obtained has also ascertained positive association between the intensity of e-business usage and cumulative e-business benefits. Despite limitations highlighted, this paper provides evidence on the current state of e-business usage across firm operation and its likely impact to the firm operation.